LEVEL KOGNITIF MORAL AUDITOR INDONESIA - Rasin Tarigan; Heru Satyanugraha (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2005)
The objective of this paper is to investigate the level of cognitive moral development of Indonesian auditors, and to find out demographic factors which differentiate the level. Defining Issues Test was used to measure the level of cognitive moral development from 100 auditors of public accounting firms in Jakarta. Result show that the level of cognitive moral development of Indonesian auditors are lower than result of previous research of auditors in USA and Hongkong. Demographic factors age, education, gender and experience do not significantly differentiate the level.